2006
DOI: 10.3171/jns.2006.104.3.369
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hypotension due to the trigeminocardiac reflex on auditory function in vestibular schwannoma surgery

Abstract: The hypotension following TCR is a negative prognostic factor for hearing preservation in patients undergoing VS surgery. Patients' knowledge of this can be increased pre- and postoperatively. Further study of this phenomenon will advance the understanding of the underlying mechanisms and may help to improve hearing preservation by controlling the occurrence of the TCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 47 publications
2
73
1
Order By: Relevance
“…From the clinical and laboratory investigations, it has been observed that nimodipine probably exerts a positive effect on the preservation of both the facial and the cochlear nerve function after VS surgery. Besides dose-dependent hypotension and its possibly intraoperative negative impact on postoperative auditory function, 5 nimodipine is a safe drug. Nimodipine's efficacy is apparently higher with regard to preservation of cochlear nerve function, especially in large tumors.…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical and laboratory investigations, it has been observed that nimodipine probably exerts a positive effect on the preservation of both the facial and the cochlear nerve function after VS surgery. Besides dose-dependent hypotension and its possibly intraoperative negative impact on postoperative auditory function, 5 nimodipine is a safe drug. Nimodipine's efficacy is apparently higher with regard to preservation of cochlear nerve function, especially in large tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations include changes in the vascular supply of the auditory apparatus. It is hypothesized, that in schwannoma patients an already impaired vascular supply of the medullo-pontine brainstem region due to tumor compression may be critically exaggerated by the sudden TCR-induced hypotension (Gharabaghi, et al, 2006). Substantiation for this hypothesis derives from the observation of BAEP deteriorations after TCR that are thought to be of vascular origin as they occur minutes after the eliciting reflex (Acioly, et al, 2010).…”
Section: Outcome and Prognosismentioning
confidence: 99%
“…TCR occurred in 11% of the patients and hearing function could be preserved in 47% of all patients. However, only 11.1% of the patients in the TCR group vs. 51.4% in the non-TCR group 13 experienced a preserved auditory function postoperatively (Gharabaghi, et al, 2006). On the basis of these results, Acioly et al (Acioly, et al, 2010) studied if intraoperatively monitored deteriorations of the brain auditory evoked potentials (BAEP) during surgery of the cerebellopontine angle were directly connected to the occurrence of TCR.…”
Section: Outcome and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous articles have described TCR during intracranial operations, ophthalmic surgery, microcompression of the trigemimal ganglion and radiofrequency lesioning of the trigeminal ganglion 3,6,[7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24] . TCR can be elicited by stimulating the afferent pathway not only from ciliary nerves but also from sensory branches of maxillary and mandibular divisions of the trigeminal nerve 15 .…”
Section: Introductionmentioning
confidence: 99%